KASHKADARYA OASIS MODERN EMBROIDERY: TRADITIONS AND INNOVATIONS (Conferencea, 2022)
National embroidery is one of the most ancient forms of folk applied art, which originated in certain historical periods due to the desire of people to beautify their homes, their lives. The study of folk embroidery as a unique art and craft is one of the modern requirements. For example, in the Yakkabag district branch of the Xujum factory in Shahrisabz, skilled embroidery, embroidery, pottery, and sewing are taught to young girls by skilled embroiderers. In the embroidery and pottery department, the girls sewed by hand. Iraqi embroidery is sewn on canvas (fabric). For example, an unlined canvas fabric is chosen for the Iraqi koshilek (20-25 cm). Before sewing, the brain is measured and a pattern called a tooth is inserted1. So we can see from this that ancient traditions continue.